Canna indica silver nanoparticles (AgNPs): a green alternative for medicine - Mathivathani Kandiah; Naiha Rizan; Beneli Gunaratne; Ominda Perera (Exploration of Drug Science)
Aim: The science of manipulating matter at almost atomic scales to create new structures and devices that function at nanoscale dimensions is known as nanotechnology, which is essential to many sciences, such as medicine and environment. This field of study has been reported to investigate better alternatives for the advancement of medicine; one such alternative is the use of plants, which contain substantial amounts of essential phytochemicals. This study aims to utilize such a plant species, Canna indica (C. indica) leaves, known as traditional medicinal plants or commonly grown plants, to synthesize silver nanoparticles (AgNPs) and evaluate their potential in green medicine. Methods: The synthesis was carried out using five varieties of leaf water extracts: Pink red, Yellow, Pink, Yellow red, and Red, under different conditions, to which scanning electron microscopy was performed. The antioxidant capacity was evaluated by total flavonoid content, total phenolic content, total antioxidant capacity, and 2,2-diphenyl-1-picrylhydrazyl radical scavenging assay. The antibacterial activity of AgNPs and water extracts was evaluated against Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli). Finally, the cytotoxicity of AgNP is evaluated using the brine shrimp lethality assay. Results: The optimum condition for AgNP synthesis was determined to be room temperature, and Pink_AgNPs were observed as spherical with a size of 27–48 nm in scanning electron microscopy. The antioxidant assays concluded that AgNPs show significantly higher antioxidant capacity and exhibit higher scavenging activity. This study’s findings showed the efficiency of AgNPs against both strains, and higher efficiency against S. aureus. It was observed that with 240 ppm of AgNPs, 100% viability is obtained. Conclusions: These novel findings emphasize the significance of C. indica AgNPs, their promise in the medical field, and their application in manufacturing green medicine for environmentally friendly healthcare.